Mechanisms and Functions of Chemerin in Cancer: Potential Roles in Therapeutic Intervention - Shin, Woo Jae; Zabel, Brian A.; Pachynski, Russell K. (Frontiers in Immunology, 2018)
Chemerin (RARRES2 [retinoic acid receptor responder 2], TIG2 [tazarotene induced gene 2]) is a multifunctional cytokine initially described in skin cultures upon exposure to the synthetic retinoid tazarotene. Its secreted pro-form, prochemerin, is widely expressed, found systemically, and is readily converted into active chemerin by various proteases. Subsequent studies elucidated major roles of chemerin as both a leukocyte chemoattractant as well as an adipokine. Chemerin’s main chemotactic receptor, the G-protein coupled receptor CMKLR1, is expressed on macrophages, dendritic, and NK cells. With respect to its role in immunology, chemerin mediates trafficking of these cells to sites of inflammation along its concentration gradient, and likely helps coordinate early responses, as it has been shown to have antimicrobial and angiogenic properties, as well. Recently, there has been mounting evidence that chemerin is an important factor in various cancers. As with its role in immune responses – where it can act as both a pro- and anti-inflammatory mediator – the potential functions or correlations chemerin has in or with cancer appears to be context dependent. Most studies, however, suggest a downregulation or loss of chemerin/RARRES2 in malignancies compared to the normal tissue counterparts. Here, we perform a comprehensive review of the literature to date and summarize relevant findings in order to better define the roles of chemerin in the setting of the tumor microenvironment and tumor immune responses, with an ultimate focus on the potential for therapeutic intervention.